2011
DOI: 10.1111/j.1365-2303.2011.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemistry for oestrogen receptor, progesterone receptor and HER2 on cell blocks in primary breast carcinoma

Abstract: Cell blocks are useful in the assessment of hormone receptor status and HER2 by IHC, especially in cases of locally advanced breast cancer for planning neoadjuvant chemotherapy. It is highly recommended to have good quality cell blocks and quality control of their interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 23 publications
4
31
4
Order By: Relevance
“…In our study, formalin-fixed cell block sections were used for breast biomarker testing. Previous studies suggested that IHCs for HER2, ER and PR performed on FFPE cell blocks were reliable in predicting the expression of these markers [18,19,20,21,22]. In our study, however, the overall change rate for ER was significantly higher in the cytological specimens than in the surgical specimens.…”
Section: Discussioncontrasting
confidence: 78%
“…In our study, formalin-fixed cell block sections were used for breast biomarker testing. Previous studies suggested that IHCs for HER2, ER and PR performed on FFPE cell blocks were reliable in predicting the expression of these markers [18,19,20,21,22]. In our study, however, the overall change rate for ER was significantly higher in the cytological specimens than in the surgical specimens.…”
Section: Discussioncontrasting
confidence: 78%
“…A study of immunohistochemically determined receptor status on cell blocks and histologic sections of breast cancer found a concordance rate of 90% for HER2/ neu results. 22 Interestingly, a more recent report 23 indicated reliability of HER2/neu assessment by dual in situ hybridization on thrombin and formalin cell block material of breast cancers, compared with IHC and FISH on histologic specimens.…”
Section: Resultsmentioning
confidence: 99%
“…For 15 patients, fine needle aspiration cytology was used to diagnose metastatic lesions. For immunohistochemical examination of cytology specimens, cell blocks were prepared using cyto-puncture materials as described by Kumar et al (5). Clinical data of the study patients were obtained from their medical records.…”
Section: Patientsmentioning
confidence: 99%